PERANCANGAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) UNTUK MENINGKATKAN LAYANAN PELANGGAN PADA TOKO UNFORGIVN TOXIC FASHION LUBUK ALUNG - Erlinda, Erlinda; Syam, Elgamar; Chairani, Sri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
A study has been done on the sales Unforgivn Toxic Fashion store regarding application development Management Customer Relationship (CRM) with the use of the website. Management Customer Relationship (CRM) is one type of management that specifically discusses the theory about the handling of the relationship between the company and its customers with the aim of increasing the company's value in the eyes of its customers. today many companies are using Management Customer Relationship (CRM) to build customer relationships. by utilizing Management Customer Relationship (CRM), companies will know what is expected and required customers that will create an emotional bond that can create strong business relationships and open and two-way communication between them.